The rate of convergence of the Hurst index estimate for a stochastic differential equation - Kubilius, Kęstutis; Skorniakov, Viktor; Ralchenko, Kostiantyn (Nonlinear Analysis: Modelling and Control, 2017)
We consider an estimator of the Hurst parameter of stochastic differential equation with respect to a fractional Brownian motion and establish the rate of convergence of this estimator to the true value of H when the diameter of partition of observation interval tends to zero.